R2N Bridging early EFL and eco-literacy: Expert validation of an eco-themed digital storybook series - Sukmawati, Ida Dian; Pujiani, Tri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
Being in disaster-risk areas frequently affected by floods, landslides, and climate change, schools increasingly seek age-appropriate ways to introduce environmental awareness while sustaining meaningful early English exposure. However, early-grade EFL classrooms often have limited resources to integrate eco-centric themes into instruction. This study aimed to establish expert-based validity evidence for an interactive eco-themed e-storybook series designed for Indonesian Grade 1 EFL learners. Using a two-round modified Delphi approach, 12 experts (teachers, language specialists, and multimedia specialists) evaluated the series through structured questionnaires and open-ended feedback, followed by targeted revisions after Round 1. Quantitative judgments were analyzed using content-validity indices (I-CVI and S-CVI/Ave) and Aiken’s V to estimate item relevance and agreement, while qualitative comments were analyzed thematically to identify revision priorities. After revision, expert judgments converged, indicating that the series is linguistically accessible for beginners, pedagogically feasible for routine-based classroom use, ecologically interpretable through child-friendly actions, and multimodally coherent when audio and interactive features remain purposeful. Qualitative feedback prioritized stronger text–image alignment for key expressions, simplified page layouts to minimize overload, improved replay and accessible glossary supports, and child-safety safeguards (e.g., ad-free, break reminder). Overall, the findings support the series as a validated instructional resource oriented to integrating early EFL learning with eco-literacy meanings.